Investigation of the thermal behaviour and dust explosion characteristics of tea powder - Nur Hikmah, Semawi (2020)
Food-based dust is considered as combustible dust as they composed of distinct particles, regardless of the size or chemical composition and when suspended in air or any other oxidizing medium over a range of concentrations and there is an ignition source will present a fire or deflagration hazard. The explosion effect from food-based dust can cause catastrophic consequences because the initial shock wave from the explosion lift up more dust and triggers a chain reaction through the plant. The parameters that can enhance the explosion are including the particle size of the dust, moisture content and minimum explosible concentration (MEC). In this research, tea powder is chosen because it tends to explode due to its molecular structure which contains a carbon-hydrogen bond that can release the significant amount of thermal energy. The chemical properties of five different particle sizes of tea powder were determined by using TGA and their effects on the dust explosion severity were tested in a confined 20 L explosion vessel. The experimental results showed that the values of Pmax and (dP/dt)max of tea powder were more severe for the particle size of 125 μm for which are 6.65 bar and 74.00 bar/s before drying and 14.61 bar and 222.00 bar/s after drying process. Its moisture content was 8.87 wt %, volatility was 60.51 wt %, fixed carbon of 25.92 wt % and ash content of 5.09 wt %. Also from the results, the concentration of 2000 g/m3 recorded the highest value for both before and drying process. It was also observed that the highest KSt value recorded was 199.60 bar.m/s and fell in class St 1. The finer dust reacted more violently than coarser ones. As particle size decreases, the rate of explosion pressure change increases, as long as the size is capable of supporting combustion and falls within the explosion limit.